Analysis of Artificial Sweeteners, Sodium Cyclamate, in Packaged Beverages and Powders by the Gravimetric Method - Pratama, Shinta Indah; Suhaenah, Asriani; Tahir, Masdiana (Pharmaceutical Reports, 2023)
Most people like instant beverage products because of their practical processing and superior taste and creative packaging, thus attracting consumers to consume them. One of the food additives that is often used in instant beverage products is artificial sweeteners such as sodium cyclamate which has a sweetness level of 3.94 kcal/g or 30 times that of sucrose. This study aims to determine the levels of sodium cyclamate in packaged and powdered drinks circulating on the campus of the Indonesian Muslim University using the gravimetric method. The sampling method used a purposive technique and obtained 6 test samples, qualitative analysis used the precipitation method and obtained all positive samples containing sodium cyclamate. The results of the quantitative analysis obtained the levels of sodium cyclamate for each sample A; B; C; D; E; F as much as 37.07 mg/kg; 30.17 mg/kg; 12.93 mg/kg; 4.31 mg/kg; 340 mg/kg; 258 mg/kg. Thus, these results indicate that all samples do not exceed the levels set by BPOM regulation No. 11 of 2019 concerning food additives, namely 350 mg/kg, so they are safe for consumption.